Waqf literatures from Malaysia: 60 years after independence - Md Dahlan, Salehudin; Mohamad, Nor Asiah (International Islamic University Malaysia, 2019)
The Article analyse and compiles various sources relating to Waqf In Malaysia and marks the first work of its kind in the subject matter